Litwa w myśli politycznej Jerzego Giedroycia - Marszał, Maciej (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
Jerzy Giedroyć is considered to be one of the most influential Polish intellectuals of the 20th century. Already in the interwar Poland, as an editor of «Bunt Młodych» and «Polityka», Giedroyć came to be known as one of the prominent Polish political thinkers. The pages of the journals constituted a platform for debate where over a dozen brilliant young writers e.g. Adolf Bocheński, Mieczysław Prószyński, Piotr Dunin – Borkowski, Jan Stanisław Łoś attempted to create a new vision of Poland. Among the topics raised by the periodicals the subject of national minorities in the Second Polish Republic appeared quite often. The real intellectual and organizational talents of Jerzy Giedroyć had revealed themselves after World War Two when he had started editing emigration monthly titled «Kultura» which for many years taught Polish people political realism and the new way of thinking about Poland, about her place in the world and her relations with neighbors. When the Polish Parliament established the year 2006 as a «year of Jerzy Giedroyć», it was a symbolic appreciation of his many contributions to the Polish cause.
Keywords: Giedroyc, Jerzy (1906-2000); myśl polityczna; Litwa